FORMATION ORGANIZATIONAL AND ECONOMIC MECHANISM MANAGEMENT DEVELOPMENT INDUSTRIAL ENTERPRISE (Development Service Industry Management, 2024)
The modern stage of the development of scientific economic thinking is characterized by a rethinking of traditional approaches and methods of system management at various levels. This is due to the need to ensure sustainable development of the enterprise in the conditions of a rapidly changing external environment, improve management efficiency, integrate innovations and maintain competitiveness on the global market. This issue is especially important for modern industrial enterprises that strive to achieve stable and long-term growth.In modern conditions, the formation of an organizational and economic mechanism consists in the creation of a complex and adaptive system that would take into account all aspects of the enterprise's activity, including resource management, the implementation of innovations, personnel development, financial planning and development integration. Overcoming these problems is necessary to ensure the long-term and management of the development of the enterprise in the conditions of the modern economy. Industrial enterprises that cannot balance their development process with the demands of the external environment lose their competitiveness and, in general, their profits. Contradictions that arise in the process of decision-making in the field of managing the development of an industrial enterprise necessitate the use of organizational and economic diagnostic mechanisms, taking into account the influence of negative trends in the external environment. The lack of effective management mechanisms of industrial enterprises will gradually lead to uncertainty in the future development, which leads to a decrease in resistance to the threat of activity in crisis conditions.The following scientists paid great attention to the study of the problem of building organizational and economic mechanisms for managing the development of industrial enterprises at the state and regional levels as V. Knorring, T. Polozova, A. Malytskyi, S. Tulchynska, L. Dovgan, N. Markova, M. Greshchak, O. Sadekov, V. Chobitok, and others. According to many scientists, the organizational and economic mechanism of managing the development of industrial enterprises is a multi-level hierarchical system of interconnected main elements and typical groups and methods of interaction.The purpose of the study is the development of theoretical and methodological foundations, as well as practical recommendations for the formation and improvement of the management mechanism for the development of an industrial enterprise.In the conditions of rapid technological changes, globalization and increased competition, industrial enterprises are faced with the need to constantly update their strategies and management methods in order to maintain their competitiveness and ensure sustainable growth. Managing the development of the enterprise requires not only flexibility and adaptability, but also a systemic approach that would cover all aspects of the enterprise's activity — from production to finance, from personnel management to marketing strategy. The economic management mechanism provides the necessary tools to achieve these goals, combining financial, investment, innovation and organizational components. The relevance of the research is determined by the need to increase its efficiency in the conditions of growing uncertainty of the external environment, global economic changes and constant improvement of technological processes. The company's ability to adapt to these challenges depends on its survival and success in the market. In this context, the research and improvement of the economic mechanism for managing the development of an industrial enterprise becomes not only a scientific and theoretical problem, but also a practical problem that requires a complex approach and the introduction of the latest management technologies.The organizational mechanism is a system of interconnected basic elements that are part of the subjects and participants of industrial enterprises or belong to the objects of their production infrastructure. The relationship between these elements should be based on the mutual exchange of resources between participants, the main condition of which should be the maximization of additional value by each participant, starting from the moment of receiving resources and processing them until the moment of their transfer to other participants. Thanks to this, the production process of the industrial enterprise is balanced and the rational use of resources is guaranteed.The formation of an organizational and economic mechanism is a critically important process for ensuring stable and sustainable growth of the enterprise in the conditions of the modern economy. This mechanism is a complex of integrated tools and approaches aimed at optimizing internal processes, efficient use of resources and adaptation to changes in the external environment. Thus, the formation of an organizational and economic mechanism for managing the development of an industrial enterprise is a dynamic process that requires an integrated approach to management, flexibility and constant improvement. The involvement of modern management methods and technologies, adaptation to changing market conditions and effective use of resources will contribute to the achievement of strategic goals and increase the competitiveness of the enterprise.
Keywords: development; management; industrial enterprise; mechanism; competitiveness